Fluidity and Lipid Composition of Membranes of Peroxisomes, Mitochondria and the ER From Oleic Acid-Induced Saccharomyces cerevisiae - Reglinski, Katharina; Steinfort-Effelsberg, Laura; Sezgin, Erdinc; Klose, Christian; Platta, Harald W.; Girzalsky, Wolfgang; Eggeling, Christian; Erdmann, Ralf (Frontiers in Cell and Developmental Biology, 2020)
The maintenance of a fluid lipid bilayer is key for organelle function and cell viability. Given the critical role of lipid compositions in determining membrane properties and organelle identity, it is clear that cells must have elaborate mechanism for membrane maintenance during adaptive responses to environmental conditions. Emphasis of the presented study is on peroxisomes, oleic acid-inducible organelles that are essential for the growth of yeast under conditions of oleic acid as single carbon source. Here, we isolated peroxisomes, mitochondria and ER from oleic acid-induced Saccharomyces cerevisiae and determined the lipid composition of their membranes using shotgun lipidomics and compared it to lipid ordering using fluorescence microscopy. In comparison to mitochondrial and ER membranes, the peroxisomal membranes were slightly more disordered and characterized by a distinct enrichment of phosphaditylinositol, indicating an important role of this phospholipid in peroxisomal membrane associated processes.